Tradisi Ratibul Hadad di Majlis Alkhairaat (Studi Living Qur’an Terhadap Q.S Al-Baqarah Ayat 285-286) - Qasim Yamani (Jurnal Multidisiplin Madani, 2022)
This paper wants to show that there are habits of the people of Palu City, especially among Abna (children) Alkhairaat who often read Ratibul Haddad. In Ratibul Haddad there are several verses of the Qur'an as reading material used as remembrance in Ratibul Haddad. Therefore, this is the author's study to see the reception of readers who read Ratibul Hadad. By using the living Qur'an method, the author wants to describe the understanding of the readers of Ratibul Haddad which is able to create peace of mind for the reader. Because Ratibul Haddad is not just reading, but in it there are remembrance that contains verses of the Qur'an. There are two similar studies regarding Ratibul Hadad including the Effect of Dhikr Ratib al-Haddad on the Mental Health of Earthquake Victims "A Case Study of Majlis Al-Ghifari Bengkulu by Sri Utami and the Effectiveness of Ratib al-Haddad on Spiritual Intelligence: Research at the Al-Mardiyah Islamic Boarding School, Cilenyi Kulon Regency Bandung by Asep Yusuf Hidayat. In conclusion, the author concludes that most of the readers of Ratibul Haddad do not know the understanding of the verses contained in these dhikrs, so they just read according to the direction of their respective teachers, even though the reading is able to give them peace of mind.